Territorial analysis of social welfare in Iran. Issue 3 (October 2015) - Mohaqeqi Kamal, Seyed Hossein; Rafiey, Hassan; Sajjadi, Homeira; Rahgozar, Mehdi; Abbasian, Ezatollah; Sharifian Sani, Maryam
Abstract : The last few decades have seen increased theoretical and empirical interest in multi-dimensional measures of social welfare. The objective of this paper is to measure social welfare in Iranian provinces. To achieve this, we used a composite social welfare index (SWI) for Iran. The SWI was developed through the methodology of constructing composite indicators. The index comprises information on different social indicators from various life domains, including: health, education, economy, social security, housing, and employment. We then categorized Iranian provinces on the basis of SWI scores. The results show that value of the SWI was poor in provinces located in the periphery of the country. Furthermore, we found the best and worst performances in Yazd and Sistan and Balochestan, respectively.